Sistem Kontrol Alarm pada Tangki Bahan Bakar - Hariningrum, Rita; Utomo, Sukarno Budi (Universitas Ivet, 2023)
A level switch is a device that detects the height or level of a volume of liquid in a tube or tank, we take an example, for example a level switch is installed in a water tank to detect the amount or volume of fuel entering the tank, then this device is connected to a pumping machine. fuel, when the volume of fuel in the tube has reached a certain level (high) and is detected by the sensor, the level switch sensor will work because the front of the level switch is submerged in oil, at that time the level switch will instruct the fuel pump engine to stop rotating, in the sense that the level switch will cut off the flow of current leading to the pumping machine. The level switch system has a fairly simple way of working. When the oil reaches half of the lower ballast (low level) then two sinkers will hang where the total weight will be able to pull the switch on the switch body at the top. The switch that is attracted to the ballast will make the relay contact close and electric current will flow through the cable to the fuel control engine which then starts and fills fuel into the tank until it reaches a high level.